The effect of limb dominance on lower limb functional performance – a systematic review. Issue 4 (16th February 2016) - McGrath, Timothy M.; Waddington, Gordon; Scarvell, Jennie M.; Ball, Nick B.; Creer, Rob; Woods, Kevin; Smith, Damian
Abstract: Lower limb dominance (or lateral preference) could potentially effect functional performance. Clinicians are often asked to make judgements as to when a patient has sufficiently "recovered" from an injury, typically using strength and dynamic performance outcome measures. The primary purpose of this study was to systematically review the literature in relation to limb dominance within active adult populations and discuss some limitations to current methods and relate this to current clinical practice. A search of MEDLINE and CINAHL and EMBASE databases and reference lists of those articles identified was performed. Eleven articles were selected for meta-analysis. There was no statistical effect of limb dominance for any of the functional tests: isokinetic quadriceps and hamstring tests, hamstring:quadriceps ratios, single-leg hop for distance, single-leg vertical jump and vertical ground reaction force following a single-leg vertical jump. Pooled symmetry values varied from 94.6% to 99.6% across the tests, above the clinically accepted benchmark of 90% used in clinical practice. Although the results of this study must be used with discretion, asymmetries in the tasks described in this analysis should be viewed as undesirable and remedied accordingly. Further research is needed to quantify asymmetries, particularly in relation to sport-specific contexts.